Observation of Writing Skill Testing of Fourth Grade Student of SD Swasta Latihan 1 YP HKBP Pematang Siantar Using the Sentence Building Method - Frans Seda Panjaitan; Duma Grace Simanjuntak; Netania Diva Sincha Saragih; Herman Herman; Asima Rohana Sinaga; Bobby Pramjit Singh Dhillon; Aprili Yanti (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to observe the process and outcomes of writing skill assessment among fourth-grade students at SD Swasta Latihan 1 YP HKBP PEMATANG SIANTAR. The background of this observation is the students’ limited ability to construct grammatically correct and structured English sentences. The teaching method used was sentence building, a technique where students are guided to form complete sentences from scrambled words provided by the teacher. This method was chosen as it is suitable for elementary-level students who are still developing basic sentence construction skills in English. The participants of this observation were all fourth-grade students. Data were collected through classroom observation, student worksheets, and reflective teacher notes. The teaching activity was conducted in stages, starting from the introduction of simple sentence patterns (Subject + Verb + Object), continued with guided sentence construction exercises, and concluded with individual writing tasks as evaluation. The observation results showed that most students demonstrated noticeable improvement in understanding sentence structure and exhibited greater confidence in writing short English sentences. Although minor errors in grammar and spelling were still present, the sentence building method proved to be effective in supporting students’ writing development. Therefore, it is recommended that this method be applied consistently in elementary-level writing instruction, especially in the context of sentence construction activities.